The butterfly effect : how your life matters - Andrews, Andy, 1959- (Simple Truths, 2009)
Building on the "butterfly theory" of Edward Lorenz, Andrews gives examples of how every move we make and every action we take, matters not just for us, but for all of us-- and for all time!